The Numerical Investigation of Fractional-Order Zakharov–Kuznetsov Equations. (27th November 2021) - Sunthrayuth, Pongsakorn; Ali, Farman; Alderremy, A. A.; Shah, Rasool; Aly, Shaban; Hamed, Y. S.; Katle, Jeevan
Abstract : In this article, a modified method called the Elzaki decomposition method has been applied to analyze time-fractional Zakharov–Kuznetsov equations. In this method, the Adomian decomposition technique and Elzaki transformation are combined. Two problems are investigated to show and validate the efficiency of the suggested method. It is also shown that the solutions achieved from the current producer are in good contact with the exact solutions to show with the help of graphs and table. It is observed that the suggested technique is to be reliable, efficient, and straightforward to implement for many related models of engineering and science.